2011
DOI: 10.1161/strokeaha.110.600221
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Tolerability of Early Noninvasive Ventilatory Correction Using Bilevel Positive Airway Pressure in Acute Ischemic Stroke

Abstract: Background and Purpose-Hypercapnia can induce intracranial blood-flow steal from ischemic brain tissues, and early initiation of noninvasive ventilator correction (NIVC) may improve cerebral hemodynamics in acute ischemic stroke. We sought to determine safety and tolerability of NIVC initiated on hospital admission without polysomnography study. Subjects and Methods-Consecutive acute ischemic stroke patients were evaluated for the presence of a proximal arterial occlusion, daytime sleepiness, or history of obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 22 publications
1
19
0
1
Order By: Relevance
“…Moreover, continuous positive airway pressure improves short-term functional outcome in stroke survivors with SA undergoing rehabilitation [24]. Apart from that, fewer publications showed feasibility and safety of early non-invasive ventilatory correction in the acute phase of stroke addressing the important association of SA and early neurological deterioration [10, 2527]. However, timely detection of vascular risk factors remains a crucial key issue when goals for secondary prevention of stroke are defined [12].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, continuous positive airway pressure improves short-term functional outcome in stroke survivors with SA undergoing rehabilitation [24]. Apart from that, fewer publications showed feasibility and safety of early non-invasive ventilatory correction in the acute phase of stroke addressing the important association of SA and early neurological deterioration [10, 2527]. However, timely detection of vascular risk factors remains a crucial key issue when goals for secondary prevention of stroke are defined [12].…”
Section: Discussionmentioning
confidence: 99%
“…We found that both the degree of sleep apnea (as indicated by the AHI) and the extent of leukoaraiosis had an unfavorable impact on functional outcome emphasizing the importance of broad vascular risk factor screening as part of routine stroke work-up in this patient population. The challenge with sleep apnea identification in the acute setting of ischemic stroke has been a lack of clinical patient selection criteria for performing specific sleep studies [17,[35][36][37]. Chronic microvascular brain tissue changes could indirectly unmask stroke patients with a long-lasting history of sleep apnea requiring focused attention and define an at-risk population that could be tested in an acute or secondary prevention clinical trial for treatment of sleep apnea [38].…”
Section: Discussionmentioning
confidence: 99%
“…However, this alternative may not be safe in patients with compromised airway patency and has not been tested in stroke patients with severe respiratory failure. 140,141 For those electing a pure palliative approach, efforts to control dyspnea, anxiety, and pain should be optimized while committing to ongoing intense care aligned with the patient's goals (which may be an intensive comfort-oriented approach). Patients with a DNI order in place should receive all other appropriate medical and surgical interventions unless otherwise explicitly indicated.…”
Section: Strokementioning
confidence: 99%